1993
DOI: 10.1177/088840649301600304
|View full text |Cite
|
Sign up to set email alerts
|

Meeting the Supply/Demand Requirements of the Individuals with Disabilities Education Act

Abstract: Some states have generated teacher supply/demand information that will satisfy the mandates of the Individuals with Disabilities Education Act. One purpose of this law is to alleviate the shortage of teachers in the field of special education. Because the supply/demand issues facing special education are closely related to those in general education, accomplishing this goal can impact on the quality of education for all children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…However, shortages do not appear to affect all schools and all classrooms in the same way. Rather, the shortage of qualified, prepared special educators available to work with students with specific disabilities, including emotional/behavioral disorders (EBDs), autism, and intellectual disabilities, as well as regional variations have been noted (Bowen & Klass, 1993; Lauritzen & Friedman, 1991, 1993; McLeskey, Tyler, & Flippin, 2004). More recently, evidence emerged that students with disabilities in high-poverty schools and districts were more likely to be taught by individuals with lesser qualifications and preparation (Fall & Billingsley, 2011; Mason-Williams, 2015), supporting what many researchers have long suggested: Teacher shortages and higher rates of attrition more often affect schools with high concentrations of poor and minority students and in exclusionary school settings (Boe, deBettencourt, Dewey, Rosenberg, Sindelar, & Leko, 2013; Brownell, Rosenberg, Sindelar, & Smith, 2004; McLeskey et al, 2004).…”
Section: Insufficient Supply and Attrition In Special Educationmentioning
confidence: 99%
“…However, shortages do not appear to affect all schools and all classrooms in the same way. Rather, the shortage of qualified, prepared special educators available to work with students with specific disabilities, including emotional/behavioral disorders (EBDs), autism, and intellectual disabilities, as well as regional variations have been noted (Bowen & Klass, 1993; Lauritzen & Friedman, 1991, 1993; McLeskey, Tyler, & Flippin, 2004). More recently, evidence emerged that students with disabilities in high-poverty schools and districts were more likely to be taught by individuals with lesser qualifications and preparation (Fall & Billingsley, 2011; Mason-Williams, 2015), supporting what many researchers have long suggested: Teacher shortages and higher rates of attrition more often affect schools with high concentrations of poor and minority students and in exclusionary school settings (Boe, deBettencourt, Dewey, Rosenberg, Sindelar, & Leko, 2013; Brownell, Rosenberg, Sindelar, & Smith, 2004; McLeskey et al, 2004).…”
Section: Insufficient Supply and Attrition In Special Educationmentioning
confidence: 99%
“…Similarly, in Philadelphia, Watson (2001) found a greater number of uncertified and inexperienced teachers and higher rates of turnover in schools with higher proportions of poor, minority students than in less diverse, low poverty schools. In terms of special education, Lauritzen and Friedman (1993) reported the simultaneous existence of shortage and excess supply in Wisconsin, sometimes in adjacent districts. In this study, shortages were severe in Milwaukee and in the remote northwest corner of the state, while slight oversupplies were noted in suburban Milwaukee and elsewhere along the Lake Michigan coastline.…”
Section: Equitable Distribution Of Teacher Supplymentioning
confidence: 99%
“…Department of Education, 2009). The limited research evidence available on the distribution of SETs indicates that regional variation in the supply exists (Lauritzen & Friedman, 1993) and that students with disabilities in high-poverty schools and districts are more likely to be taught by individuals with lesser qualifications and preparation (Fall & Billingsley, 2008Peske & Haycock, 2006). Although data available from the Data Accountability Center (www.ideadata.org) demonstrated that the proportion of SETs considered highly qualified increased to 94% by fall 2011 (U.S. Department of Education, 2012), questions remain regarding the extent to which schools rely on substitute teachers, the number of positions left unfilled, and the qualifications of indirect service providers who do not need to meet highly qualified teacher (HQT) requirements (Steinbrecher, McKeown, & Walther-Thomas, 2013).…”
mentioning
confidence: 99%